PENGETAHUAN SISWA TENTANG SEKS PRANIKAH DI SMA NEGERI 1 BERASTAGI TAHUN 2017 - Susanti br Perangin-angin (Jurnal Ilmiah PANNMED (Pharmacist, Analyst, Nurse, Nutrition, Midwivery, Environment, Dentist), 2017)
Sexuality issues until recently an interesting topic that is always discussed. One of the sexual problems that are often discussed premarital sex. Negative impact of premarital sex is very disturbing society. Dai recent survey in 33 provinces in 2008 by the National Family Planning Coordinating Board (BKKBN) reported 63% of adolescents in Indonesia between the ages of SMP and high school already having sexual relations outside marriage. The percentage of teens who had sexual intercourse before marriage has increased compared to previous years. This study aims to determine the level of knowledge of students of SMA Negeri 1 Berastagi Karo District Berastagi about premarital sex. Research is descriptive research, sample number as many as 50 people. Sampling technique using total sampling technique that is all the population sampled data was collected using questionnaires and interviews. Data analysis using desscriptive statistics. Test results of students' level of knowledge of SMA Negeri 1 Berastagi Karo District Berastagi regarding premarital sex by 58% were categorized with poor knowledge. From the results of these studies are expected to the school and parents can play an active role in providing information on reproductive health and sex education to the students.